Transformation of Lampung Natural Zeolite into Zeolite-A by Aluminium Addition and Application as Catalyst for Biomass Pyrolysis - Syayyidati Aulia; Wasinton Simanjuntak; Kamisah Delilawati Pandiangan; Mita Rilyanti (Purnomo Yusgiantoro Center, 2024)
In this study, the transformed zeolite from Lampung natural zeolite (LNZ) was used as a catalyst for the pyrolysis of a mixture of cassava tubers and rubber seed oil to produce bio crude oil (BCO). Transformation of Lampung natural zeolite into zeolite-A was attempted by adjusting the Si/Al ratios to 1.0, 1.5, and 2.0 transformed with and without aluminum addition and hydrothermal method with variation Si/Al ratio of 1.0; 1.5 and 2.0. The resulting products were specified as Zeo-C, Zeo-R1, Zeo-R1.5 and Zeo-R2.0. XRD analysis results show that Zeo-C and Zeo-R2 were transformed into zeolite-P, while zeolite-A, as targeted, was found in Zeo-R1 and Zeo-R1.5. SEM analysis results were also in accordance with XRD analysis results that showed the bipyramid crystal of zeolite-P in Zeo-C and Zeo-R2, while the cubic crystal of zeolite-A in Zeo-R1 and Zeo-R1.5. The BCO produced by using Zeo-C and Zeo-R1.5 as catalysts has the highest hydrocarbon content of 81% and 98%, respectively. Compared to previous studies, our study introduces an innovative approach by utilizing LNZ, a resource that has not been extensively explored, and combining cassava and rubber seed oil to produce bio-crude oil with a high hydrocarbon content. Our study contributes by promoting the use of underutilized biomass resources, potentially providing an environmentally friendly and economically viable alternative for BCO production.